Radiotherapy planning in a prostate cancer phantom model with intraprostatic dominant lesions using stereotactic body radiotherapy with volumetric modulated arcs and a simultaneous integrated boost - Skrobala, Agnieszka; Kruszyna-Mochalska, Marta; Graczyk, Kinga; Ryczkowski, Adam; Fundowicz, Magdalena; Milecki, Piotr; Malicki, Julian (Frontiers in Oncology, 2023)
Aim. In the treatment of prostate cancer with radiation therapy, the addition of a simultaneous integrated boost (SIB) to the dominant intraprostatic lesions (DIL) may improve local control. In this study, we aimed to determine the optimal radiation strategy in a phantom model of prostate cancer using volumetric modulated arc therapy for stereotactic body radiotherapy (SBRT-VMAT) with a SIB to 1-4 DILs. Methods. We designed and printed a three-dimensional anthropomorphic phantom pelvis to simulate individual patient structures, including the prostate gland. A total of 36.25 Gy (SBRT) was delivered to the whole prostate. The DILs were irradiated with four different doses (40, 45, 47.5, and 50 Gy) to assess the influence of different SIB doses on dose distribution. The doses were calculated, verified, and measured using both transit and non-transit dosimetry for patient-specific quality assurance using a phantom model. Results. The dose coverage met protocol requirements for all targets. However, the dose was close to violating risk constraints to the rectum when four DILs were treated simultaneously or when the DILs were located in the posterior segments of the prostate. All verification plans passed the assumed tolerance criteria. Conclusions. Moderate dose escalation up to 45 Gy seems appropriate in cases with DILs located in posterior prostate segments or if there are three or more DILs located in other segments.